GE_GERICHTE C/18059/2008 vom 18. November 2014 - GE Cour de justice (2014)
SOCIÉTÉ(GROUPEMENT DE PERSONNES ET DE CAPITAUX); SÛRETÉS; ENTREPRENEUR EN RAISON INDIVIDUELLE | aLPC.102; aLPC.103; CPC.103; CPC.238.F; Cst.29.1